Buffer Sizing in Critical Chain Method in Case of Binomial Probability Distribution of Task Duration - Bieniecki, Marian (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
An attempt of critical chain method for project consisted of special tasks has been applied. The probability distribution of such a task duration is discrete, particularly binomial. The sizing of appropriate path buffer has been suggested. The possibility of early buffer exceeding warning has been noticed.